2011
DOI: 10.2478/v10019-011-0017-4
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of low iodine diet in managing patients with differentiated thyroid cancer - initial results

Abstract: BackgroundLow iodine diet (LID) is recommended in patients with differentiated thyroid cancer before radioiodine administration. Patients with increased thyroglobulin (Tg) level, but negative 131I whole body scan present diagnostic and therapeutic dilemma. This study was designed to evaluate the benefit of a two-week LID in patients with elevated serum Tg levels and negative 131I whole body scans.Patients and methods.For the impact assessment of two-week LID on radioiodine tissue avidity, radioiodine scans bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
(18 reference statements)
0
8
0
2
Order By: Relevance
“…Some studies revealed the association between a low iodine diet and ablation therapy. Choi et al showed that 24-h urine iodine excretion was significantly lowered after a stringent low iodine diet in Korean patients with thyroid cancer [28], and Dobrenic et al reported that a more stringent low iodine diet might result in higher radioiodine avidity in patients undergoing I-131 ablation therapy [29]. Maurice et al showed the percentage of patients with successful ablation was significantly high in the low iodine diet group compared with the normal diet group [30].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies revealed the association between a low iodine diet and ablation therapy. Choi et al showed that 24-h urine iodine excretion was significantly lowered after a stringent low iodine diet in Korean patients with thyroid cancer [28], and Dobrenic et al reported that a more stringent low iodine diet might result in higher radioiodine avidity in patients undergoing I-131 ablation therapy [29]. Maurice et al showed the percentage of patients with successful ablation was significantly high in the low iodine diet group compared with the normal diet group [30].…”
Section: Discussionmentioning
confidence: 99%
“…There are very limited data in the literature about the changes of TSH and thyroid hormones during pregnancy in patients with a history of thyroid carcinoma. To our knowledge, these studies included only a small number of patients 8 , 12 15 with the largest study group of 18 such cases reported by Loh et al . 8 There are scarce data about the optimal increase of L-thyroxine dose during pregnancy in the patients with thyroid carcinoma after total thyroidectomy and radioiodine ablation of thyroid remnant.…”
Section: Introductionmentioning
confidence: 99%
“…However, all of them suggested restriction of all kinds of seafood, milk and dairy products, instant food or commercial products (dressing, packaged rice…) [5,[14][15][16][17]. In this article, most of the guidelines on low iodine diet were updated by Korean researches from 2012 to 2016 [14,15] and the newest guideline from United Kingdom (2018) [18].…”
Section: Discussionmentioning
confidence: 99%